176 Malignant Primary Spinal Column Tumors: Prognostic Significance of HTERT (Human Telomerase Reverse Transcriptase) Promoter Region Mutations C228T and C250T for Overall Survival. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Bettegowda, Chetan; Yip, Stephen; Jiang, Bowen; Wang, Wei-Lien; Clarke, Michelle J; Lazary, Aron; Gambarotti, Marco; Zhang, Ming; Sciubba, Daniel M; Wolinsky, Jean-Paul; McCarthy, Edward; Germscheid, Niccole; et al.
Abstract: INTRODUCTION: Primary spinal column malignancies are rare tumors with poor prognosis, few systemic treatment options, and limited understanding of the molecular drivers of neoplasia. METHODS: Study design was a retrospective review of prospectively collected data. An initial cohort of 1495 patients with primary spinal column tumors were treated at 13 centers within Europe, North America, and Australia between December 1985 and January 2013. Information regarding patient mortality was acquired cross-sectionally. Archived paraffin-embedded pathological specimens were available for 133 patients from 6 of the 13 centers. Tumor DNA was extracted from the paraffin specimens and the hTERT promoter was sequenced using Sanger Sequencing. The hTERT mutational status was correlated to overall survival (OS). RESULTS: Ninety-two chordomas, 26 chondrosarcomas, 7 osteosarcomas, 3 Ewing's sarcomas, and 5 other malignant spinal tumors were analyzed. Eight chordomas, 2 chondrosarcomas, 1 Ewing's sarcoma, and 1 other malignant spinal tumor harbored either a C228T mutation or a C250T mutation in the hTERT promoter. Median OS following surgery was 5.8 yr (95% confidence interval [CI] 4.6-6.9), and median time to first local recurrence was 3.9 yr (95% CI 2.5-6.7). OS was worse in the Enneking grade II tumor group ( P = .047). After controlling for standard demographic and clinical criteria, including adequacy of surgical resection and adjuvant therapy, hTERT mutational status was associated with improved survival. One hundred percent of patients with hTERT mutation were alive at 10 yr postoperative as compared to approximately 24% of patients who lacked the mutation ( P = .031). CONCLUSION: We report for the first time that hTERT promoter mutations C228T and C250T are present in approximately 10% of spinal chordomas. In addition, all individuals with the hTERT mutations were alive at 10 yr postoperative compared to 24% of those lacking the mutations. Future prospective studies are required to further elucidate the role of hTERT promoter mutations in primary spinal column malignancies.